Internal anal sphincter nerves – a macroanatomical and microscopic description of the extrinsic autonomic nerve supply of the internal anal sphincter. (3rd January 2018) - Stelzner, S.; Böttner, M.; Kupsch, J.; Kneist, W.; Quirke, P.; West, N. P.; Witzigmann, H.; Wedel, T.
Abstract: Aim: The internal anal sphincter (IAS) contributes substantially to anorectal functions. While its autonomic nerve supply has been studied at the microscopic level, little information is available concerning the macroscopic topography of extrinsic nerve fibres. This study was designed to identify neural connections between the pelvic plexus and the IAS, provide a detailed topographical description, and give histological proof of autonomic nerve tissue. Methods: Macroscopic dissection of pelvic autonomic nerves was performed under magnification in seven (five male, two female) hemipelvises obtained from body donors (67–92 years). Candidate structures were investigated by histological and immunohistochemical staining protocols to visualize nerve tissue. Results: Nerve fibres could be traced from the anteroinferior edge of the pelvic plexus to the anorectal junction running along the neurovascular bundle anterolaterally to the rectum and posterolaterally to the prostate/vagina. Nerve fibres penetrated the longitudinal rectal muscle layer just above the fusion with the levator ani muscle (conjoint longitudinal muscle) and entered the intersphincteric space to reach the IAS. Histological and immunohistochemical findings confirmed the presence of nerve tissue. Conclusions: Autonomic nerve fibres supplying the IAS emerge from the pelvic plexus and are distinct to nerves entering the rectum via the lateral pedicles. Thus, they should be classified as IAS nerves. The identification and precise topographical location described provides a basis for nerve‐sparing rectal resection procedures and helps to prevent postoperative functional anorectal disorders.